2017
DOI: 10.1007/s12275-017-6311-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial compound produced by Pseudomonas aeruginosa strain UICC B-40, an endophytic bacterium isolated from Neesia altissima

Abstract: This study's aim was to determine the identity of antibacterial compounds produced by Pseudomonas aeruginosa strain UICC B-40 and describe the antibacterial compounds' mechanisms of action for damaging pathogenic bacteria cells. Isolation and identification of the compounds were carried out using thin layer chromatography (TLC), nuclear magnetic resonance (NMR) spectroscopy and liquid chromatography mass spectrometry (LC-MS) analyses. Antibacterial activity was assayed via minimum inhibitory concentration (MIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…In addition, the differences between the gene clusters responsible for the phenazines biosynthesis among different Streptomyces species (13) that may lead to the diverse phenazine structural derivatives produced by the bacteria at different levels (39). Although phenazines are generally isolated from Pseudomonas, Streptomyces and several other microbial genera from soil and marine habitats, however, many endophytic Streptomyces species associated with various plants are also capable in producing this secondary metabolite compounds (12,13). This suggests that the endophytic microbial group is one source of potential natural sources in the discovery of new antimicrobial compounds.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the differences between the gene clusters responsible for the phenazines biosynthesis among different Streptomyces species (13) that may lead to the diverse phenazine structural derivatives produced by the bacteria at different levels (39). Although phenazines are generally isolated from Pseudomonas, Streptomyces and several other microbial genera from soil and marine habitats, however, many endophytic Streptomyces species associated with various plants are also capable in producing this secondary metabolite compounds (12,13). This suggests that the endophytic microbial group is one source of potential natural sources in the discovery of new antimicrobial compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Isolation of bioactive compound. Isolation of antibacterial compound from actinomycetes was conducted according to the method described by Pratiwi et al (12) and Saha et al (22) as follows: selected endophytic actinomycetes strain that showed highest antagonistic activity was sub-cultured on ISP2 medium and incubated for 7 days. Spores of the endophytic actinomycetes strain were inoculated into 500 mL of ISP2 broth medium (pH 6.75) in a 1 L Erlenmeyer flask and incubated in shaking incubator (100 rpm) at room temperature for 5 days.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Member of Pseudomonas are described as non allergenic, non-pathogenic, and non toxic toward people, wild life or domestic animal. Pseudomonas also has great potential on producing antibiotic bioactive potential such as indole derivatives, phenazines, pyrrolnitrin-type antibiotics, glycolipids, another substances (Pratiwi et al, 2017). Wu et al (2018) evaluated P. aeruginosa L10 as biosurfactant producing and excellent hydrocarbondegrading bacteria isolated from roots, stems and leaves of a Reed Phragmites australis).…”
Section: Discussionmentioning
confidence: 99%